From Resilience to Vulnerability: Mechanistic Insights into the Effects of Stress on Transitions in Critical Period Plasticity - Callaghan, Bridget L.; Graham, Bronwyn; Li, Stella; Richardson, Rick (Frontiers in Psychiatry, 2013)
While early experiences are proposed to be important for the emergence of anxiety and other mental health problems, there is little empirical research examining the impact of such experiences on the development of emotional learning. Of the research that has been performed in this area, however, a complex picture has emerged in which the maturation of emotion circuits is influenced by the early experiences of the animal. For example, under typical laboratory rearing conditions infant rats rapidly forget learned fear associations (infantile amnesia) and express a form of extinction learning which is relapse-resistant (i.e., extinction in infant rats may be due to fear erasure). In contrast, adult rats exhibit very long-lasting memories of past learned fear associations, and express a form of extinction learning that is relapse-prone (i.e., the fear returns in a number of situations). However, when rats are reared under stressful conditions then they exhibit adult-like fear retention and extinction behaviors at an earlier stage of development (i.e., good retention of learned fear and relapse-prone extinction learning). In other words, under typical rearing conditions infant rats appear to be protected from exhibiting anxiety whereas after adverse rearing fear learning appears to make those infants more vulnerable to the later development of anxiety. While the effects of different experiences on infant rats’ fear retention and extinction are becoming better documented, the mechanisms which mediate the early transition seen following stress remain unclear. Here we suggest that rearing stress may lead to an early maturation of the molecular and cellular signals shown to be involved in the closure of critical period plasticity in sensory modalities (e.g., maturation of GABAergic neurons, development of perineuronal nets), and speculate that these signals could be manipulated in adulthood to reopen infant forms of emotional learning (i.e., those that favor resilience).